Struktur dan Diksi Teks Anekdot Siswa Kelas X SMKN 1 Kelayang Kabupaten Indragiri Hulu Riau - Cindy Nurmalenia; Ermawati Arief (Universitas Maritim AMNI Semarang, 2023)
The purpose of this study was to describe the structure and use of diction in anecdotal texts for class X students of SMKN 1 Kelayang. This type of research is a qualitative research with descriptive method. The data of this study are the structure and diction accuracy of anecdotes. The data source used in this study was anecdotal texts by class X students of SMKN 1 Kelayang for the 2022/2023 academic year. The data collection technique in this study is the fishing technique. Analyzing the research data, namely by means of data reduction, data presentation, and data verification. The results of this study are as follows. First, in writing anecdotal texts, class X students of SMKN 1 Kelayang used the five anecdotal text structures, namely abstract, orientation, crisis, reaction, and coda. Most students are able to write anecdotal texts with a complete structure. However, there are still some structures that students write incorrectly. Second, it was found that the accuracy of diction was more dominant based on writing errors, formation and accuracy of meaning in the writing of class X students of SMKN 1 Kelayang.